Household access to basic drinking water, sanitation and hygiene facilities: secondary analysis of data from the demographic and health survey V, 2017-2018 - Nicolas Gaffan; Alphonse Kpozèhouen; Cyriaque Dégbey; Yolaine Glèlè Ahanhanzo; Romain Glèlè Kakaï; Roger Salamon (BMC, 2022)
Abstract Background In Benin, access to water, sanitation and hygiene (WASH) remains an issue. This study aims to provide an overview of household access to basic WASH services based on nationally representative data. Method Secondary analyses were run using the 'HOUSEHOLD' dataset of the fifth Demographic and Health Survey 2017-2018. The dependent variables were household access to individual and combined basic WASH services. The characteristics of the household head and those related to the composition, wealth and environment of the household were independent variables. After a descriptive analysis of all study variables, multivariate logistic regression was performed to identify predictors of outcome variables. Results The study included 14,156 households. Of these, 63.98% (95% CI = 61.63-66.26), 13.28% (95% CI = 12.10-14.57) and 10.11% (95% CI = 9.19-11.11) had access to individual basic water, sanitation and hygiene facilities, respectively. Also, 3% (95% CI = 2.53-3.56) of households had access to combined basic WASH services. Overall, the richest households and few, and those headed by people aged 30 and over, female and with higher levels of education, were the most likely to have access to individual and combined basic WASH services. In addition, disparities based on the department of residence were observed. Conclusion The authors suggest a multifactorial approach that addresses the identified determinants.